(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Coronavirus disease 2019 (COVID-19) outbreak firstly occurred in Wuhan, China, and quicklyspread worldwide causing global public health threats. Bacterial and fungal infections are reportedly the common secondary infections correlated to viral pneumonia and lead to severe complications particularly in critically ill patients. This complication could lead to an increase in the demands for intensive care, and consequently increasing the rate of deaths. Despite the importance of these complications, few published articles reported a secondary infection, in particular those caused by fungi. Secondary infections were detected in 50% of COVID-19 patients who did not survive.Mucormycosis or called “black fungus”caused by the fungus mucormycete, significant fungal infection that fundamentally affects individuals who suffer from health problems or occupy medicines that lower the ability of the body to fight against germs and illnesses. So, in this review, we highlighted the currently available articles of secondary fungal infection related to COVID-19 infected patients. Thus, the current study rises the attention to the importance of fungal secondary infection, particularly from previously epidemics caused by the virus corona such as MERS and SARS) –COV diseases.